Study Deskriptif tentang Gaya Hidup Modern Mahasiswa dalam Memelihara Kesehatan Ginjal - Handoyo Handoyo; Herry Prasetyo; Hartati Hartati (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2026)
ABSTRACT Background. The kidneys are vital organs that function to filter blood and remove metabolic waste. The consumption pattern of ultra-processed food (UPF) and unhealthy drinking habits can put an excessive burden on kidney function. Health students, although they have knowledge about kidney health, do not necessarily implement consumption behaviors that support the maintenance of kidney function. Methods. This study used a descriptive quantitative approach with a survey method of 45 nursing students from the Nursing Study Program in Purwokerto City. Data were collected using a questionnaire that had been tested for validity and reliability, then analyzed descriptively. Results. The results showed that 82.2% of respondents consumed ultra-processed food more than three times a week, and 73.3% had met the daily water consumption needs of ± 2 liters. The habit of consuming ultra-processed foods can have a negative impact on kidney health. This condition can be worsened when they also pay less attention to drinking at least 1.5-2 liters of mineral water per day. Conclusion. There are habits of nursing students in drinking water to support kidney health, but not for the habit of consuming ultra-processed food. Therefore, educational interventions and healthy campus policies are needed to encourage changes in consumption behavior. Keywords: life style, student, health, kidneys.